2022
DOI: 10.21608/mid.2022.147680.1334
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Monkeypox Research: A Sixty Year Bibliometric Analysis

Abstract: Aim:The purpose of the study was to identify common descriptors and publication hotspots that may form reference themes for future monkey pox research. Method: Bibliometric analysis of monkeypox related studies between 1962 and 2022 was carried out to ascertain and describe this body of literature. Results and conclusion: A total of 1,134 documents were analysed for bibliometric indicators. The studies had 3,478 authors, an average of 5.72 coauthors per publication and a 3.73 author collaboration index. Annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Keyword co-occurrence analysis can yield a wealth of useful information, allowing the identification of hot spots and trends and directing researchers to similar topics in their field (35). Three distinct MARV research topics can be identified, which mostly involve issues of epidemiology and public health, pathogenicity and vaccine development, and immunology and molecular biology, and commensurate effort by research scientists is compulsory for effective MVD prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Keyword co-occurrence analysis can yield a wealth of useful information, allowing the identification of hot spots and trends and directing researchers to similar topics in their field (35). Three distinct MARV research topics can be identified, which mostly involve issues of epidemiology and public health, pathogenicity and vaccine development, and immunology and molecular biology, and commensurate effort by research scientists is compulsory for effective MVD prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest authorship collaboration networks were formed by the US-CDC, the University of Kinshasa, and the National Institute of Biomedical Research, with moderate links formed by the other organizations. Rodriguez-Morales, Ortiz-Martinez, and Bonilla-Aldana [6] assessed monkeypox-related research using four databases up to December 31, 2021. Cheng, Zhou, and Wu [7] analyzed 566 global publications on MPXV-related research until May 21, 2022, identifying key countries, organizations, and authors, and the collaborative linkages between them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The database is one of the most comprehensive for bibliometric and patentometric analysis. It contains millions of publications cited over 1.6 billion times linked with patents,clinical trials,policy documents, datasets and grants [15,17]. This database is completely inclusive of PubMed, making it highly reliable.…”
Section: Data Acquisition and Query Criteriamentioning
confidence: 99%
“…Cite space, and visualization of similarities (VOS) are the most popular bibliometric analysis tool for knowledge mapping via bibliometrics [14]. Knowledge mapping has been applied in many research fields [13,15,16]. To date, a knowledge mapping analysis of AMR research contributions and inclinations in Nigeria has remained hidden.…”
Section: Introductionmentioning
confidence: 99%